INSTABILITY OF LEGAL REGULATION OF ECONOMIC ACTIVITY AS A FACTOR OF CRIME DETERMINATION - Сисоєва, Вікторія Петрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: the purpose of scientific research is to identify certain dangerous economic and legal factors related to the instability of legal regulation of economic activity and their impact on crime in the economic sphere in Ukraine. Methods: used general scientific and special scientific methods, namely - comparative-legal, system-structural, documentary, etc. Results: the influence of legal factors on the state economy and crime rate is analyzed. Measures to eliminate such factors are proposed. Instability of the state regulatory policy of any economic activity due to changes in the legislation causes a constant state of imbalance, and can cause confusion and inaccuracies in the interpretation of legal acts and create conditions for violating the requirements of the legislator and avoiding liability for this dishonesty. Adding to this the corruption and influence of the "shadow" sector on the economy of our country, it becomes evident that today, businesses engaged in economic activity, it is difficult to choose the right path of business development. Discussion: the article is devoted to the study of legal factors and their impact on crime in the field of economic activity. Due to the implementation of socially and economically sound policy, when regulatory acts regulating economic activity are adopted interrelated, but not individually, the causes of crime in this area are eliminated. The economy of our country is regulated unreasonably by a large number of legal acts, which are sometimes contradictory. Legal examination of such regulatory documents is not carried out at the proper level, and criminological analysis is not carried out at all. Similarly, taking into account the interests of all market participants, rather than lobbying individual groups of entrepreneurs, has a preventive effect in the field of crime prevention.